Violence against wives, sexual risk and sexually transmitted infection among Bangladeshi men. - Silverman, Jay G; Decker, Michele R; Kapur, Nitin A; Gupta, Jhumka; Raj, Anita (Sexually transmitted infections, 2007)
To assess the relationship between men's reported violence against wives and their sexual risk behaviours and sexual health. Design,
Keywords: Adolescent; Adult; Bangladesh; Cross-Sectional Studies; Extramarital Relations; Female; Humans; Male; Middle Aged; Prevalence; Regression Analysis; Risk-Taking; Rural Health; Sexually Transmitted Diseases; Spouse Abuse; Urban Health